Kelakuan Seks Bebas di Kalangan Remaja Melayu - Awang, Idris (Jurnal Usuluddin, 1997)
The study is an attempt to identify the causes that lead to the phenomenum of free sex among the youngsters in the Klang Valley. The data were collected from the sample of youngsters who frequented public places, namely, shopping complexes in Klang Valley and Merdeka Square in Kuala Lumpur. The study identifies that the causes are: too much freedom, simple attitude towards sex, peer’s influence, the influence of mass media, easy accessibility to entertainment centres, unstable family relationship, easy availability of birth control facilities and lack of religious education.